The Role of the Family in Forming Worship Habits in Adolescents (JIRE: Journal of Islamic Religious Education, 2025)
The family plays a significant role in shaping worship habits in teenagers. As the first social environment, the family contributes to instilling religious values, guiding children in carrying out worship, and providing examples in everyday life. Islamic education emphasizes the importance of forming religious character from an early age so that children are able to carry out religious commands well. However, in the digital era, the challenges in forming worship habits are increasingly complex due to the influence of technology, social media, and the wider social environment. This research uses library research methods by analyzing various sources, including journals, books, and scientific articles, to understand the role of the family in forming worship habits. The data obtained were compared with previous findings to develop a more comprehensive analysis. The results of the discussion show that religious education in the family plays a key role in shaping the Islamic character of adolescents. Being accustomed to worship from an early age, receiving emotional support from parents, and participating in the religious community are important factors in ensuring the consistency of worship. Apart from that, holistic religious education and collaboration between family, school, and community contribute to the formation of a strong religious character